Inventing the Market - Herzog, Lisa (UK Oxford University Press, 2016)
Inventing the Market explores two paradigms of the market in the thought of Adam Smith and G.W.F. Hegel, bridging the gap between economics and philosophy, it shows that both disciplines can profit from a broader, more historically situated approach to the market.
Include Index and Bibliography
Keywords: Political science--Philosophy -- Smith, Adam -- Economics--Philosophy